(untitled) (Journal of history, 2021)
Age is researched. It is stated that from the bases of Sauromatian tribes that lived in the early Iron Age emerged the Sarmatian tribes in Mid Iron Age, i.e. the tribes in question are from the same root. Moreover, by proving through archaeological finds the existence of such tribes in the region, the axes that were uncovered from kurgans in the region are evaluated. Part of the finds from the Kurgan excavations which forms weapons, gives important information on the dating of the buried in the Kurgan and monitoring the spread of nomadic tribes’ geography. Therefore, the chronological typology of the weapons uncovered from the kurgans found in Northern Black Sea, the North Caucasus and Russia territories was constructed by scientists, relative to this, the construction of chronological typology of the weapons of nomadic tribes found in west Kazakhstan is needed. Therefore, in this study we have addressed, based on the experience of previous researchers before us, considering the old and new information the typology of the uncovered axes from the Sauromat-Sarmatian kurgans is being constructed and its historical process is being considered. Key words: Sauromat, Sarmat, South Ural, West Kazakhstan, kurgan, ax